Visual methodology in graphic design: report of a didactic experience in teaching-learning (Revista de Ensino em Artes, Moda e Design, 2022)
The objective of this study is in the theoretical discussion of the elements of visual language presented by Dondis (1997); Lupton and Phillips  (2008); Gomes Filho (2009); Heller (2013); Bergström  (2009); Leborg (2015) and other theorists who  dialogue with them. The purpose is in the practical  demonstration in the classroom of how such  fundamentals are relevant in the creative process of  graphic compositions. The research emphasizes the  premise that the graphic designer, when mastering  the visual language, understanding each of its  constitutive elements, has better mastery, skill and  creativity to develop graphic projects with good  formal composition and high pregnancy of form. The  methodology adopted was the bibliographic research  and the case study. The results are the  result of creative activities developed in the  classroom with students from the graphic design  course at UFG. From theoretical studies on the  elements of composition and visual organization,  dozens of graphic pieces were created by the  students through the experimental method using  different techniques and materials.
Keywords: Elements of visual language; Gestalt; Pregnancy of form